STOP1 regulates the expression of HsfA2 and GDHs that are critical for low-oxygen tolerance in Arabidopsis. (18th March 2019) - Enomoto, Takuo; Tokizawa, Mutsutomo; Ito, Hiroki; Iuchi, Satoshi; Kobayashi, Masatomo; Yamamoto, Yoshiharu Y; Kobayashi, Yuriko; Koyama, Hiroyuki
Abstract : The Arabidopsis stop1 mutant is sensitive to low-oxygen stress and this is attributable to decreases in inducible expression of GDH s and HsfA2, which are critical for low-oxygen tolerance. Abstract: The SENSITIVE TO PROTON RHIZOTOXICITY 1 (STOP1) transcription factor regulates gene expression associated with multiple stress tolerances in plant roots. In this study, we investigated the mechanism responsible for the sensitivity of the stop1 mutant to low-oxygen stress in Arabidopsis. Transcriptomic analyses revealed that two genes involved in low-oxygen tolerance, namely GLUTAMATE DEHYDROGENASE 1 ( GDH1 ) and GDH2, showed lower expression levels in the stop1 mutant than in the wild-type. Sensitivity of the gdh1gdh2 double-mutant to low-oxygen conditions was partly attributable to the low-oxygen sensitivity of the stop1 mutant. Two transcription factors, STOP2 and HEAT SHOCK FACTOR A2 ( HsfA2 ), were expressed at lower levels in the stop1 mutant. An in planta complementation assay indicated that CaMV35S :: STOP 2 or CaMV35S :: HsfA2 partially rescued the low-oxygen tolerance of the stop1 mutant, which was concomitant with recovered expression of genes regulating low-pH tolerance and genes encoding molecular chaperones. Prediction of cis -elements and in planta promoter assays revealed that STOP1 directly activated the expression of HsfA2 . Similar STOP1-dependent low-oxygen sensitivity was detected in tobacco. Suppression of NtSTOP1 induced low-oxygen sensitivity, which was associated with lower expression levels of NtHsfA2 and NtGDH s compared with the wild-type. Our results indicated that STOP1 pleiotropically regulates low-oxygen tolerance by transcriptional regulation.